A 'strong enough' father. Observations from groups for expectant and new fathers. Issue 2 (20th September 2019) - Cenerini, Marco Vieri; Messina, Danilo
ABSTRACT: The paper describes groups for expectant fathers and new fathers led by the authors, in which they discuss many aspects of fatherhood and becoming fathers. Differences are considered between the physical and emotional process which expectant mothers go through the pregnancy develops with the psychological one for fathers, whose expectancy is in the realm of the mind, the imagination and of the stirring up of strong feelings. The paper explores the significance of fathers' contribution to the baby's emotional and psychological development, highlighting the significance of the expectant father's contribution as recipient of the pregnant mother's wordless communications, through projective identification, acting as a container, and later his contribution to the mother and baby's successful separations, often starting with weaning, and later in other ways. The father's different role from mother is discussed not only in the traditional idea of the firm, boundary-setting parent, but also and in relation to the mother–father–child triangle.